Resposta da cultura do girassol a doses de potássio, magnésio, boro, zinco, cobre e a fontes de nitrogênio - Queiroga, Fábio Martins de (Universidade Federal Rural do Semi-Árido, 2011)
In the northeast semi-arid, the culture of the sunflower can be cultivated under regime of rains or under irrigation conditions in the period of the drought. In Agropolo Mossoró- Assú, an important melon and watermelon production area in irrigation conditions during the drought period, the sunflower comes with high potential for culture rotation during the rainy period. However, the sunflower will only be economically viable if be obtained high productivities, what depends a lot on an appropriate fertilization. In this work it was aimed evaluating the answer of the sunflower culture (Helianthus annuus L.) to levels of K (potassium), Mg (magnesium), B (boron), Zn (zinc), Cu (copper) and to different sources of N (nitrogen) applied in the planting and in covering in alkaline soil of the Chapada do Apodi-RN. Two field trials were carried out in the municipal district of Baraúna-RN, in a clay eutrophic Haplic Cambisol. The sunflower was sowed in the spacing of 0,90 x 0,30 m using the hybrid H-251. The trial design had randomized blocks with four replications. In the trial 1, 10 treatments were compared with your respective nutrient applications to the soil, with five levels of K (0; 25; 50; 75 and 100 kg ha-1) and five levels of B (0,0; 0,5, 1,0; 2,0 and 3,0 kg ha-1). In the trial 2, seven treatments were compared with the objective of evaluating the effects of the presence and absence of the fertilization with Zn, Cu and Mg and the effects in different use forms (planting and, or, covering) of sources of N (urea and, or, ammonium sulfur). 47 days after emergency (DAE), samples composed of soil were collected in the depth from 0 to 20 cm of the useful area of each portion, for determination of the content of K, Mg, B, Zn and Cu available. In the beginning of the flower development of the sunflower, the nutritional status of the plants was evaluated, being determined the content of N, P, K, Ca, S, Mg, Zn, B and Cu in the leaves. At the end of the trial, plant height, stem and chapter s diameter, mass of 1.000 grains and the yield of grains were evaluated. The application of K and B doses increased the levels of those nutrients ones in the soil, however there was not effect in the plant as well as the characteristics of the sunflower plant related to the growth and the production. The treatments of presence and absence of a dose of Zn, Cu and Mg didn't influence the characteristics of the sunflower plant related to the growth and the production. The N fertilization of the sunflower culture, using different sources of N applied in the planting and in covering, didn't influence the level of N in the leaf and the characteristics of the sunflower plant related to the growth and the production.
Answer of the sunflower growth to doses of potassium, magnesium, boron, zinc, copper and sources of nitrogen
Keywords: Sunflower; oilseed; potassium; boron; Girassol; oleoginosa; potássio; boro; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO